How is health literacy addressed in primary care? Strategies that general practitioners use to support patients. (2nd October 2018) - Hedelund Lausen, Lisa; Smith, Sian K.; Cai, Antonia; Meiser, Bettina; Yanes, Tatiane; Ahmad, Raghib; Rowlands, Gillian
ABSTRACT: Background: Low health literacy is associated with adverse health outcomes and raises healthcare costs. General practitioners (GPs) are the first point of access to health care services and play a key role in building patients' health literacy level. This study aimed to explore: (1) GPs' understanding of health literacy, (2) their perceived challenges to addressing health literacy, and (3) the strategies they used to support patients with health literacy difficulties. Method: This qualitative study was conducted in South Western Sydney, New South Wales, Australia. Semi-structured interviews were audio-recorded and transcribed verbatim. Interview data were analyzed using the Framework method, a matrix-based approach to thematic analysis. Results: Eighteen participants took part in the study. Four key themes were identified: (1) identifying patients with health literacy difficulties; (2) perceived consequences of low health literacy; (3) being sensitive to developing health literacy skills; and (4) strategies used to build health literacy. Intuitive skills were used to identify the patient's health literacy skills through recurring encounters with patients over time. A range of communication techniques were used to build health literacy. The value of a long-term relationship with patients and support from relatives were reported (Please eliminate this comma and the one right before this) to be important in helping patients build their health literacy skills. Conclusions: A number of challenges in health literacy exist in general practice. General practitioners can play a role in overcoming these challenges by placing an increased focus on health literacy, including self-education on this topic, identification of patients with low health literacy skills and helping build patients' level of health literacy.